Konstruksi Tematik Ayat-Ayat Hukum (Konsep dan Dasar Seleksi Ayat Hukum Menurut Al-Tahawi) - Siregar, Ahmad Sholihin; Nuruddin, Amiur; Qorib, Ahmad (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
This research begins from unavailability of basis in selecting legal verses. Therefore, this research aims to construct foundation of selecting legal verses starting from the selection done by al-Tahawi. This research is a normative law research (doctrinaire, dogmatic). The research object is legal verses of alTahawi’s selection found in Ahkam al-Qur’an. The object is approached by using mimetic and objective approach. There are two foundations used by al-Tahawi in selecting legal verses; textually and contextually. The textual foundation consists of the availability or unavailability of mukallaf action in a verse. The contextual foundation consists of asbab al-nuzul and explaining hadis. From the selection basis, the characteristic of legal verses is also constructed textually and contextually. The textual characteristic consists of key words showing law content such as: la junaha, laisa haraj, urrima, uhilla, kutiba, faridah, al-salat, al-saum, al-zakah, al-hajj, ar-rafas. Contextual characteristic consists of: asbab al-nuzul of a legal verse should be related to a legal matter; and there are explaining hadis showing the existence of law content in certain verses